1976
DOI: 10.1083/jcb.70.1.9
|View full text |Cite|
|
Sign up to set email alerts
|

Dependence of centriole formation on protein synthesis.

Abstract: Centriole formation was studied after inhibition of protein synthesis for various portions of the cell cycle. Synchronous populations of mitotic L929 (mouse) cells were plated into petri dishes and the course of procentriole formation was monitored by electron microscope analysis. The frequency with which procentrioles were seen in association with mature centrioles normally increased steadily in the interval from 4 to 12 h after mitosis. The formation of procentrioles was abruptly inhibited by the addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

1978
1978
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 32 publications
0
14
1
Order By: Relevance
“…We found that simultaneous treatment of U2OS/centrin-GFP cells with 1 mM HU and 5 mg/ml CHX for 72 h efficiently reduced the proportion of cells with centriole overduplication from 45 to 4.7% (9.6-fold; Pp0.0005; Figure 3a). In contrast to a previous report (Phillips and Rattner, 1976), we found an increase of cells with duplicated centrioles in asynchronously growing populations that were treated with CHX alone. Such increase was not seen in cells treated with a-amanitin alone or transfected with CBP siRNAs and may be related to the fact that CHX can induce a G2 cell cycle arrest leading to an accumulation of cells with duplicated centrioles.…”
Section: A-amanitin Inhibits Hpv-16 E7-and Hu-induced Centriole Overdcontrasting
confidence: 99%
“…We found that simultaneous treatment of U2OS/centrin-GFP cells with 1 mM HU and 5 mg/ml CHX for 72 h efficiently reduced the proportion of cells with centriole overduplication from 45 to 4.7% (9.6-fold; Pp0.0005; Figure 3a). In contrast to a previous report (Phillips and Rattner, 1976), we found an increase of cells with duplicated centrioles in asynchronously growing populations that were treated with CHX alone. Such increase was not seen in cells treated with a-amanitin alone or transfected with CBP siRNAs and may be related to the fact that CHX can induce a G2 cell cycle arrest leading to an accumulation of cells with duplicated centrioles.…”
Section: A-amanitin Inhibits Hpv-16 E7-and Hu-induced Centriole Overdcontrasting
confidence: 99%
“…The report that protein synthesis in late G~ is required for daughter centriole formation in cultured cells (20), may raise questions about the applicability of our results to somatic cells. In this regard, the important finding of our study is that the synthesis of new proteins, such as structural components or regulatory enzymes, at each cell cycle is not a strategy used by all cells to control centrosome reproduction.…”
Section: Discussionmentioning
confidence: 68%
“…For cultured L929 (mouse) cells, at least 4 h of protein synthesis in late G, is required for procentriole formation (20). However, this study is subject to the criticism that inhibition of protein synthesis arrests the cell cycle before the point when procentriole assembly is scheduled to occur.…”
mentioning
confidence: 88%
“…Because multiple duplication cycles proceed in X. laevis or sea urchin embryos in which protein synthesis is prevented (Gard et al, 1990;Sluder et al, 1990), centrosome duplication does not necessarily require a given protein to be synthesized at each cell cycle, even though protein synthesis is required for duplication in somatic cells (Phillips and Rattner, 1976). Since centrosome duplication is coupled to DNA replication, S phase might be permissive for duplication and, by extension, centrosome duplication might take place once per cell cycle merely because there is a single S phase.…”
Section: Building a Daughter Centriolementioning
confidence: 99%